Ibuprofen-conjugated hyaluronate/polygalacturonic acid hydrogel for the prevention of epidural fibrosis. (May 2016) - Lin, Cheng-Yi; Peng, Hsiu-Hui; Chen, Mei-Hsiu; Sun, Jui-Sheng; Chang, Chih-Ju; Liu, Tse-Ying; Chen, Ming-Hong
The formation of fibrous tissue is part of the natural healing response following a laminectomy. Severe scar tissue adhesion, known as epidural fibrosis, is a common cause of failed back surgery syndrome. In this study, by combining the advantages of drug treatment with a physical barrier, an ibuprofen-conjugated crosslinkable polygalacturonic acid and hyaluronic acid hydrogel was developed for epidural fibrosis prevention. Conjugation was confirmed and measured by 1D 1 H NMR spectroscopy. In vitro analysis showed that the ibuprofen-conjugated polygalacturonic acid–hyaluronic acid hydrogel showed low cytotoxicity. In addition, the conjugated ibuprofen decreased prostaglandin E2 production of the lipopolysaccharide-induced RAW264.7 cells. Histological data in in vivo studies indicated that the scar tissue adhesion of laminectomized male adult rats was reduced by the application of our ibuprofen-conjugated polygalacturonic acid-hyaluronic acid hydrogel. Its use also reduced the population of giant cells and collagen deposition of scar tissue without inducing extensive cell recruitment. The results of this study therefore suggest that the local delivery of ibuprofen via a polygalacturonic acid-hyaluronic acid-based hydrogel reduces the possibility of epidural fibrosis.